The Effect of Cervical Paravertebral Extensor Degeneration on Sagittal Alignment and Functional Status of Cervical Spine in Patients With Cervical Spondylotic Myelopathy. Issue 7 (August 2021) - Yang, Peng; Wen, Bingtao; Ge, Rile; Liu, Xin; Tan, Lei; Zhong, Jun; Jin, Kaiji; Chen, Zhongqiang
Abstract : Study Design: This was a cross-sectional study. Objective: The objective of this study was to assess cervical paravertebral extensor degeneration in patients with cervical spondylotic myelopathy (CSM) and its impact on the sagittal parameters and functional status of the cervical spine. Summary of Background Data: Paravertebral extensor degeneration is well-studied in CSM; however, the effect of extensor degeneration on the sagittal balance and functional status of the cervical spine is unclear. Materials and Methods: We enrolled 52 CSM patients (CSM group) and 52 age-matched and sex-matched healthy adults (control group). The C2–C7 and C0–C2 Cobb angles (CAs), C7 slope, T1 slope, cervical arc cord distance, cervical tilt (CERT), cranial tilt (CRAT), and C2–C7 sagittal vertical axis (SVA) were measured. The cross-sectional areas of the deep extensors (DEA), superficial extensors (SEA), and cervical vertebral body (VBA) of C4–C7 were measured. DEA/VBA and SEA/VBA were used to quantify the extensor volume. We analyzed the fatty infiltration ratio of the deep (DFIR) and superficial extensors (SFIR). The Visual Analog Scale, Neck Disability Index, and modified Japanese Orthopaedic Association Scale scores of the CSM group were calculated. Results: The DEA/VBA was significantly lower and the DFIR and SFIR were significantly higher in the CSM group. The C4 DEA/VBA correlated with the C2–C7 SVA, C2–C7 CA, CERT, and the Neck Disability Index and modified Japanese Orthopaedic Association Scale scores ( r =−0.608, 0.291, 0.335, −0.649, and 0.409, respectively). The DEA/VBA of C5 correlated with the cervical arc cord distance and CRAT ( r =−0.350 and −0.356, respectively). The C4 DFIR correlated with the C2–C7 SVA, C2–C7 CA, and the Visual Analog Scale ( r =0.286, −0.297, and 0.429, respectively). The SFIR of C7 correlated with the T1 slope and C7 slope ( r =0.368 and 0.319, respectively). Conclusions: Paravertebral extensor degeneration negatively impacts the sagittal sequence and functional status of the cervical spine in CSM patients. Our study provides an insight into understanding the significance of cervical muscular degeneration in CSM patients. Level of Evidence: Level III.